(untitled) (Transmediterranean History, 2022)
This article analyses a treaty which was negotiated by the Mamlūk sultan al-Ašraf Ḫalīl (r. 689–693/1290–1293) and King James II of Aragon (r. 1291–1327) in 1293. It begins with a discussion of the treaty’s authorship and provenance and then describes the context in which the treaty emerged. Here, special attention is paid to the convergence of commercial and political interests relating to both the Crown of Aragon and the Mamlūk Sultanate of Cairo. The article closes with a cursory analysis of the treaty’s clauses and reflects on their implications for transmediterranean relations.